GOVERNMENT CREDIT GUARANTEE (GCG) FOR THE IMPROVEMENT OF PEOPLE AT THE BOTTOM OF THE ECONOMIC PYRAMID - SUBKHAN NA (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2018)
The main objective of this study is to measure the impact of Government Credit Guarantee (GCG) scheme on household poverty alleviation. This study employed a cross-sectional design with purposive random sampling method to examine whether participation in GCG programs improves the hardcore poor households quality of life. To analyze the impact of GCG scheme on household poverty reduction, this study uses logistic regression model. The findings confirmed that households participating in GCG programs tend to have higher probability in reducing their poverty condition compared with those who have no access to GCG programs. The reduction in household poverty can be described by the improvement in their monthly income, improvement in monthly food expenditures, and improvement in monthly non-food expenditure. Therefore, Indonesian Government should review, re-organize and improve the GCG programs and policies in order to increase the outreach and improve client's ability to receive higher amount of loan through GCG scheme.A. Introduction